Dropout Analysis of a National Social Health Insurance Program at Pokhara Metropolitan City, Kaski, Nepal - Prabin Sharma; Dipendra Yadav; Niranjan Shrestha; Prabesh Ghimire (Kerman University of Medical Sciences, 2022)
Background  Nepal's national social health insurance (SHI) program, which started in 2016, aims to achieve universal health coverage (UHC), but it faces severe challenges in achieving adequate population coverage. By 2018, enrolment and dropout rates for the scheme were 9% and 38% respectively. Despite government's efforts, retaining the members in SHI scheme remains a significant challenge. The current study therefore aimed to assess the factors associated with SHI program dropout in Pokhara, Nepal.Methods  A cross-sectional household survey of 355 households enrolled for at least one year in the national SHI program was conducted. Face-to-face interviews with household heads were conducted using a structured questionnaire. Data was entered in Epi-Data and analysed using SPSS. The factors associated with SHI program dropout were identified using bivariate and multiple logistic regression analyses.Results  The findings of the study revealed a dropout prevalence of 28.2% (95% CI: 23.6%-33.2%). Households having more than five members (adjusted odds ratio [aOR]: 2.19, 95% CI: 1.22-3.94), belonging to underprivileged ethnic groups (Dalit/Janajati) (aOR: 2.36, 95% CI: 1.08-5.17), living on rented homes (aOR: 4.53, 95% CI: 1.87-10.95), absence of chronic illness in family (aOR: 1.95, 95% CI: 1.07-3.59), perceived good health status of the family (aOR: 4.21, 95% CI: 1.21-14.65), having private health facility as first contact point (aOR: 3.75, 95% CI: 1.93-7.27), poor availability of drugs (aOR: 4.75, 95% CI: 1.19-18.95) and perceived unfriendly behaviour of service providers (aOR: 3.09, 95% CI: 1.01-9.49) were statistically significant factors associated with SHI dropout.Conclusion  In Pokhara, more than one-fourth of households have dropped out of the SHI scheme, which is a significant number. Dropping out of SHI is most commonly associated with a lack of drugs, followed by rental housing, family members' reported good health status and unfriendly service provider behaviour. Efforts to reduce SHI dropout must focus on addressing drugs availability issues and improving providers' behaviour towards scheme holders. Increasing insurance awareness, including provisions to change first contact points, may help to reduce dropouts among rented households, which make up a sizable proportion of the Pokhara metropolitan area.